Transfers from prison to hospital under Sections 47 and 48 of the Mental Health Act between 2011 and 2014 - Sharpe, Robert; Völlm, Birgit; Akhtar, Amina; Puri, Ramneesh; Bickle, Andrew (Taylor & Francis, 2016)
In England and Wales, prisoners with mental disorder of such severity as to warrant inpatient treatment may be transferred to hospital under the Mental Health Act. UK Government guidance recommends that this process should be completed within 14 days; however, evidence suggests that in many cases it can take much longer. This retrospective service evaluation of 64 male prisoners, who were transferred under Section 47 or Section 48, aimed to evaluate transfer durations. The mean time from referral to admission was 76 days. Prisoners with a psychotic disorder were admitted more quickly. Remand prisoners were admitted more quickly than sentenced prisoners. Findings suggest that, in the UK the transfer time of prisoners under Sections 47 and 48 of the Mental Health Act continues to far exceed the 14-day target which raises concern about equivalence of care for prisoners. Our findings support arguments for fundamental amendments to the admissions process.